Communication and Community in a City Under Siege : The AIDS Epidemic in San Francisco - ROGERS, EVERETT M. and DEARING, JAMES W. and RAO, NAGESH and CAMPO, SHELLY and MEYER, GARY and BETTS, GARY J. F. and CASEY, MARY K. (Communication Research, 1995)
The history of urban life has been shaped and directed by the impact of disaster and disease, variables that have not disappeared in the postmodern age. Certainly, a deadly epidemic destroys and alters communication relationships while at the same time creating new communication needs and possibilities. The structure, social institutions, and policies of cities in part determine the impact and response to affliction. The authors analyze how the city of San Francisco was disrupted by the AIDS epidemic and how HIV / AIDS prevention campaigns sought to slow the epidemic. Both the epidemic and the communication response to it altered socially constructed notions about community through changes in personal behavior, interpersonal behavior, and organizational activities in San Francisco.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwOTUwMjIwMDYwMDU